V 홈 바닥에 형성된 일차원 InAs 양자점 - 손창식; 최인훈; 박용주 (한국재료학회, 2003)
One-dimensional array of InAs quantum dots (QDs) have been grown on V-grooved GaAs substrates by low-pressure metalorganic chemical vapor deposition. Atomic force microscope images show that InAs QDs are aligned in one-dimensional rows along the [011] oriented bottom of V-grooves and no QDs are formed on the sidewalls and the surface of mesa top. Capability to grow one-dimensional InAs QDs array would feasible for the single electron tunneling devices and other novel quantum-confined devices.